Clarifying the chemical reactions of the weakening of adhesion between epoxy resin and aluminum by molecular dynamic simulation and experiment - Wang, Jian; Wang, Zhe; Yan, Ningning; Han, Zhiyun; Chang, Yanan; Wang, Jingrui; Li, Qingmin (Frontiers in Materials, 2022)
We have established a cross-linked epoxy resin model and a composite model of epoxy resin and aluminum at the molecular level. Based on ReaxFF, the reaction molecular dynamics simulation of pyrolysis aging was carried out by Lammps. The aged epoxy resin is decomposed into H2, CO, H2O, CO2, CH4 and CH2O. Tensile simulation of aged epoxy resin and aluminum system was carried out, and the stress-strain curve was obtained. Compared with non-agingg, the maximum stress is reduced by 25.77%. In order to verify the correctness of the simulation results, an epoxy resin with Diglycidyl ether of Bisphenol A (DGEBA) as the resin substrate and 4,4 '- Diaminodiphenyl sulfone (44DDS) as the curing agent was prepared, which is coated on the surface of aluminum for curing. In order to explore the change of adhesion during aging, we put the samples in high-temperature vacuum drying oven at 160℃ for thermal oxygen aging experiment. The state of epoxy resin at different aging time was studied by SEM, XPS and FTIR. The results showed that the adhesion decreased by 27.16% after aging. The chemical bond in epoxy resin was seriously damaged, the content of the O/C element increased from 15.95% to 22.76%, and the surface cracks of epoxy resin coating increased significantly. Through molecular dynamics simulation and thermal aging experiments, this paper reveals the reasons for the reduction of adhesion between epoxy resin and aluminum caused by thermal aging, which provides theoretical guidance for the actual engineering change of epoxy resin.